The Role of Midwives in Postpartum Health Monitoring to Reduce the Risk of Postpartum Complications - Mariyatul Qiftiyah; Siti Maria Ulfa; Puji Hastuti; Mega Octamelia (PT. Anagata Sembagi Education, 2024)
This research aims to explore the role of midwives in postpartum health monitoring and its impact on reducing the risk of postpartum complications. Postpartum complications, such as infections, bleeding, and mental health disorders, remain significant health challenges for mothers following childbirth. The study utilizes a quantitative survey method to measure the relationship between midwifery interventions and the occurrence of these complications. Data were collected from 260 postpartum mothers who received care from midwives, with a focus on the frequency of visits, types of services provided, and health outcomes. The findings suggest that regular postpartum monitoring by midwives significantly reduces the risk of complications, highlighting the importance of early detection, education, and ongoing support. This research contributes to understanding the effectiveness of midwifery care and provides recommendations for improving healthcare policies related to maternal health.